2013
DOI: 10.1038/bjc.2013.742
|View full text |Cite
|
Sign up to set email alerts
|

p53-dependent and p53-independent anticancer effects of different histone deacetylase inhibitors

Abstract: Background:Histone deacetylase inhibitors (HDACi) are promising antineoplastic agents, but their precise mechanisms of actions are not well understood. In particular, the relevance of p53 for HDACi-induced effects has not been fully elucidated. We investigated the anticancer effects of four structurally distinct HDACi, vorinostat, entinostat, apicidin and valproic acid, using isogenic HCT-116 colon cancer cell lines differing in p53 status.Methods:Effects were assessed by MTT assay, flow-cytometric analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 47 publications
5
60
0
Order By: Relevance
“…S5F). These findings are consistent with a recent report from Sonnemann et al (2014), showing that HDAC inhibition in HCT116 cells is partially dependent on p53.…”
Section: Direct Effects Of Hdac Inhibition On Cell Growth and Survivalsupporting
confidence: 94%
“…S5F). These findings are consistent with a recent report from Sonnemann et al (2014), showing that HDAC inhibition in HCT116 cells is partially dependent on p53.…”
Section: Direct Effects Of Hdac Inhibition On Cell Growth and Survivalsupporting
confidence: 94%
“…Likewise, we have recently observed that the SIRT1/2 inhibitor tenovin-1 effectively killed p53 +/+ , but not p53 −/− cancer cells (Sonnemann et al 2014), further substantiating that the effects of sirtuin modulators can depend on p53. To consider a potential impact of p53 on the response of ES cells to STACs, we used three ES cell lines differing in their p53 status, viz.…”
Section: Single-agent Activity Of Resveratrol and Srt1720 Against Ewisupporting
confidence: 58%
“…HDACi activated P53, and entinostatinduced cytotoxic effects partially depended on P53 in colon cancer cell lines (25). Valproic acid and TSA affect acetylation status of p53 and induce apoptosis in ERG-positive prostate cancer cells (26).…”
Section: Discussionmentioning
confidence: 99%